Comparison of Quadrantic Retinal Nerve Fiber Layer Thickness between Glaucoma Patients and Age Matched Controls: Doi: 10.36351/pjo.v37i3.1199 - Ashraf, Nargis Nizam; Siyal, Nisar Ahmed; Ibrahim, Muhammad (Pakistan Journal of Ophthalmology, 2021)
Purpose: To compare the quadrantic retinal nerve fiber layer thickness between the glaucoma patients and age-matched controls. Study Design: Descriptive observational study. Place and Duration of study: Eye Department of Civil Hospital Karachi, from January 2018 to December 2020. Methods: Two hundred and fifty eyes were included in this study. There were 128 eyes of the glaucoma patients and 122 eyes were age-matched controls. After complete ocular examination, all participants underwent optical coherence tomography and retinal nerve fiber layer thickness measurement in four quadrants. Prior quadrants were subsequently analyzed. Heidelberg 3-D optical coherence tomography 2017, Spec- TR- 04859 was used. Readings were saved on Excel sheet and analyzed on SPSS version 25. For descriptive statistics the mean and standard deviations were calculated for each quadrant and for inferential statistics the data was first checked for the normality. Comparison of the quadrants was done using non-parametric Paired Sample t-test (Wilcoxon signed rank test). Results: Out of 250. Form which 128 (51%) eyes were those of glaucoma patients and 122 (49%) eyes were of non-glaucoma patients. The mean difference between the Glaucomatous and non-Glaucomatous eyes were statistically significant in all four quadrants (p > 0.05). Conclusion: Glaucomatous eyes had reduced RNFL thickness in all quadrants. The thickness of the inferior quadrant was more as compared to the other quadrants in both glaucoma and control groups. Whereas the least thickness was that of the temporal quadrant. Key Words: Retinal nerve fiber layer, Optical coherence tomography, Glaucoma.